A computational parametric study on edge loading in ceramic-on-ceramic total hip joint replacements. (July 2018) - Liu, Feng; Feng, Li; Wang, Junyuan
Abstract: Edge loading in ceramic-on-ceramic total hip joint replacement is an adverse condition that occurs as the result of a direct contact between the head and the cup rim. It has been associated with translational mismatch in the centres of rotation of the cup and head, and found to cause severe wear and early failure of the implants. Edge loading has been considered in particular in relation to dynamic separation of the cup and head centres during a gait cycle. Research has been carried out both experimentally and computationally to understand the mechanism including the influence of bearing component positioning on the occurrence and severity of edge loading. However, it is experimentally difficult to measure both the load magnitude and duration of edge loading as it occurs as a short impact within the tight space of hip joints. Computationally, a dynamic contact model, for example, developed using the MSC ADAMS software for a multi-body dynamics simulation can be particularly useful for calculating the loads and characterising the edge loading. The aim of the present study was to further develop the computational model, and improve the predictions of contact force and the understanding of mechanism in order to provide guidance on design and surgical factors to avoid or to reduce edge loading and wear. The results have shown that edge loading can be avoided for a low range of translational mismatch in the centres of rotation of the cup and head during gait at the level of approximately 1.0 mm for a cup at 45° inclination, keeping a correct cup inclination at 45° is important to reduce the edge loading severity, and edge loading can be avoided for a certain range of translational mismatch of the cup and head centres with an increased swing phase load. Highlights: A model using the Adams software to simulate dynamic separation and edge loading in ceramic total hip joint replacements. The stiffness coefficient of contact model was determined. Friction associated with the experimental simulator mechanism was studied. The effect of translational mismatch in the centres of rotation of the cup and head (0–4 mm) on edge loading was studied. Edge loading may be avoided for the cup at a correct inclination with a low level of translational mismatch.